Validation Study of the Composite Score to Identify Von Willebrand Disease in Children. Issue 2 (March 2016) - Malec, Lynn M.; Moore, Charity G.; Bennett, Carolyn M.; Yee, Donald L.; Kerlin, Bryce A.; Witmer, Char M.; Kulkarni, Roshni; Gupta, Sweta; Gunawardena, Sriya; Kouides, Peter A.; Brown, Deborah; Ragni, Margaret V.
Abstract : Background: The diagnosis of type 1 von Willebrand disease (VWD) presents a diagnostic challenge in children. In fact, 25% or more of children with VWD may be diagnosed only after they experience postoperative bleeding. We previously described a 4-variable composite score that has 92.5% sensitivity and 95% specificity for diagnosing VWD in children with known VWD when 2 of 4 criteria are positive: (1) Tosetto bleeding score ≥1; (2) family history of VWD; (3) personal history of iron deficiency anemia; and/or (4) positive James early bleeding score. The purpose of this study was to prospectively validate a composite score of ≥2 for identifying children with VWD. Procedure: Children without a previously diagnosed bleeding disorder presenting for hematology evaluation were enrolled. Sensitivity, specificity, positive, and negative predictive value of the composite score was determined. Results: A total of 193 subjects were enrolled from 12 participating centers were included in the analysis. Forty-seven children had type 1 VWD, including 11 with von Willebrand Ristocetin Cofactor (VWF):RCo <30 IU/dL, 14 subjects with a VWF:RCo 30 to 39 IU/dL, and 22 with a VWF:RCo 40 to 49 IU/dL. Including all 4 variables, a composite score of ≥2 had a sensitivity of 63.6% to 76.0%, specificity of 33.5% to 35.1%, negative predictive value of 76.9% to 93.8%, and positive predictive value of 5.5% to 25%. Conclusions: The negative predictive value of the composite score was robust, especially at lower VWF:RCo suggesting that VWD testing could be eliminated in nearly a third of children referred for VWD testing. Abstract : Supplemental Digital Content is available in the text.